Efektivitas Metode Snowball Throwing dalam Keterampilan Menyimak untuk Menentukan Pokok Berita Siswa Kelas VIII SMP Negeri 4 Watampone Kabupaten Bone - Muh Safar (CV. Syntax Corporation Indonesia, 2022)
This study aims to determine the effectiveness of using the snowball throwing method in listening learning to find news headlines for class VIII students of SMP Negeri 4 Watampone Bone Regency. The approach in this research is descriptive quantitative and the design or experimental design used in this research is the Rondomized Control-Group Test Only Design. The population in this study were all eighth grade students of SMP Negeri 4 Watampone, Bone Regency. While the samples were students of class VIII A as the control class and students of class VIII B as the experimental class. The data collection technique in this study was a test technique in the form of multiple choice questions and descriptions. The results of the t-test calculation show that the t-count value is 4.1680, which is greater than the 1% significant level for dk=64. The t-table is 2.386. Thus, it shows that t-count > t-table is 4.1680 > 2.386 so that at the level of 1% the data obtained is very significant, then the Ho hypothesis is rejected. It can be concluded that listening learning to find the main news using the snowball throwing method is effectively applied to class VIII students of SMP Negeri 4 Watampone, Bone Regency. This can be seen from the average value of the control class of 74.25 and the average result of the experimental class of 83.8529. The conclusion of this research is that the snowball throwing method is effectively used in learning to listen to news stories for class VIII of SMP Negeri 4 Watampone, Bone Regency.